Ursodeoxycholic Acid Protects Against Arsenic Induced Hepatotoxicity by the Nrf2 Signaling Pathway - Li, Chao; Zhang, Sheng; Li, Liming; Hu, Qing; Ji, Shen (Frontiers in Pharmacology, 2020)
Arsenic is ubiquitous toxic metalloid responsible for many human diseases all over the world. Contrastingly, Ursodeoxycholic acid (UDCA) has been suggested as efficient antioxidant in various liver diseases. However, there are no reports of the effects of UDCA on arsenious acid (As(Ⅲ))-induced hepatotoxicity. The objective of this study is to elucidate the protective actions of UDCA on As(Ⅲ)-induced hepatotoxicity and explore its controlling role in biomolecular mechanisms in vivo and in vitro. The remarkable liver damage induced by As(Ⅲ) was ameliorated by treatment with UDCA, as reflected by reduced histopathological changes of liver and elevation of serum AST, ALT levels. UDCA play a critical role in stabilization of cellular membrane potential, inhibition of apoptosis and LDH leakage in LO2 cells. Meanwhile, the activities of SOD, CAT and GSH-Px and the level of TSH, GSH were enhanced with UDCA administration, while the accumulations of intracellular ROS, MDA and rate of GSSG/GSH were decreased in vivo and in vitro. Further study disclosed that UDCA significantly inhibited As(Ⅲ)-induced apoptosis through increasing the expression of Bcl-2 and decreasing the expression of Bax, p53, Cyt C, Cleaved caspase-3 and 9. Moreover, UDCA promoted the expression of nuclear Nrf2, HO-1, and NQO1, although arsenic regulated nuclear translocation of Nrf2 positively. When Nrf2 was silenced, the protective effect of UDCA was abolished. Collectively, the results of this study showed that UDCA protects hepatocytes antagonize As(Ⅲ)-induced cytotoxicity, and its mechanism may be related to activation of Nrf2 signaling.